KAJIAN SENI LUKIS KARYA YUNUS SUNARTO - S. Suyadi; D. Dharsono (Institut Seni Indonesia Surakarta, 2015)
The research entitled â€œKajian Seni Lukis Karya Yunus Sunartoâ€ (A Study in Paintings Arts by Yunus Sunarto)aims: to know about the background of creative process in painting arts by Yunus Sunarto; to analyze theform of paintings art by Yunus Sunarto using analysis interpretation with aesthetic approach by MonroeBeardsley; and to learn the observerâ€™s view towards paintings art by Yunus Sunarto. Data is collected byobservation, interview, and library studies. The six paintings by Yunus Sunarto, with the studies of analysisinterpretative and aesthetic approach by Monroe Beardsley, refer to the three aesthetic characteristics ofarts: unity, there are visual and design elements well composed in the paintings; complexity, an art is not sosimple but it is rich of content and contains a smooth difference. Intensity, an art has an outstanding qualityeven in a bleak, happy, soft and rough condition. In reconstructing natural events, the aesthetic form ofYunus Sunartoâ€™s paintings has a proportional form of anatomy, gradation, and volume in painting an object incanvas even the color sometimes seems tacky.Keywords: paintings art, works, aesthetic, creativity